URBAN LAND REGULARIZATION AS A MECHANISM FOR THE ENFORCEMENT OF FUNDAMENTAL RIGHTS AND THE PROMOTION OF REGIONAL DEVELOPMENT - Rossi, Elaine Cristina Juliano; Oliveira, Guilherme Resende (Seven Editora, 2025)
The present article examines Urban Land Regularization as an instrument for the realization of fundamental rights and the promotion of regional development, situating it within the Brazilian historical and normative trajectory (sesmarias, Land Law, 1988 Constitution, City Statute, Laws No. 11,977/2009 and 13,465/2017) and within the right to the city and the social function of property. This research has a qualitative approach, with bibliographic and documentary research, to test the hypothesis that Urban Land Regularization, when conceived as a structuring and territorialized public policy, transforms housing into a concrete right, integrates informal settlements into urban planning, and activates local socioeconomic capacities, aligning itself with the goals of the 2030 Agenda (SDGs 1, 6, 9, 10, 11, and 16). The objective is to evaluate the extent to which land regularization, articulated with urbanistic, environmental, and social justice criteria, reduces territorial asymmetries, increases legal certainty, and strengthens multilevel governance. The results indicate that Urban Land Regularization produces positive impacts on social inclusion, tax collection, and investment in infrastructure, in addition to qualifying land use and climate adaptation. However, it requires safeguards to avoid speculative captures, as well as monitoring metrics and priority for Social Interest Regularization. It is concluded that Urban Land Regularization should be treated as a State policy (transdisciplinary and participatory) capable of articulating rights, organizing the territory, and promoting sustainable regional cohesion. DOI: https://doi.org/10.56238/sevened2025.036-102